Encountering Development: The Making and Unmaking of the Third World - Sulistyani, Wanodyo (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2014)
The Westernâs lack of understanding of the local reality of the Third World was the alleged cause of the failure of development programs over the Third World. This book challenges this premise by seeing the problems from the perspective of not only the recipient countries, associated with the Third World or underdeveloped countries; but also from the donor, associated with the Western or developed countries. Encountering development means that both sides should not neglect the realities or challenges that exist in the process of development. All realities, such as political, social, cultural, history, the use of technology and science, must be taken into consideration when creating strategies for development. Finally, compromise between both parties through âhybrid culturesâ model needs to be established in order to maintain the development.Â DOI: https://doi.org/10.22304/pjih.v1n1.a11